ANALYSIS OF PROFITABILITY AND LIQUIDITY AT XYZ INSURANCE BROKER IN THE PERIOD OF 2019-2020 - Fahmi, Darul (Sean Institute, 2022)
This study aims to analyze the liquidity and profitability of XYZ Insurance Broker during the 2019-2020 period. By assessing the company’s financial performance through key financial ratios such as the Current Ratio, Quick Ratio, Cash Ratio, Profit Margin, Return on Investment (ROI), and Return on Equity (ROE), this research provides insight into the company’s ability to meet short-term obligations and generate profits. The research utilized both primary and secondary data, gathered through interviews with the company's finance department and documentation in the form of financial reports. The findings indicate that XYZ Insurance Broker has made improvements in its liquidity and profitability, although the results are still below industry standards. While the Current and Quick Ratios have shown some improvement, the Cash Ratio and Cash Turnover Ratio have significantly declined, indicating the need for better cash and receivables management. Profitability has also improved, with increases in the Net Profit Margin and ROE, but the figures remain below industry expectations. To achieve optimal financial performance, XYZ Insurance Broker needs to implement more aggressive strategies, including enhancing operational efficiency, improving working capital management, and diversifying products and services. These efforts are expected to improve the company's liquidity and profitability in the future, aligning it with industry standards.